Regulation of Endoplasmic Reticulum Stress-Autophagy: A Potential Therapeutic Target for Ulcerative Colitis - Qiao, Dan; Zhang, Ziwei; Zhang, Yali; Chen, Qian; Chen, Yujun; Tang, Yingjue; Sun, Xiong; Tang, Zhipeng; Dai, Yancheng (Frontiers in Pharmacology, 2021)
Ulcerative colitis (UC) is a chronic nonspecific inflammation that mainly affects the mucosa and submucosa of the rectum and colon. Numerous studies have shown that endoplasmic reticulum stress (ERS)-induced autophagy plays a vital role in the pathogenesis of UC. ERS is the imbalance of internal balance caused by misfolded or unfolded proteins accumulated in the endoplasmic reticulum (ER).Excessive ERS triggers the unfolded protein response (UPR), an increase in inositol-requiring enzyme 1, and a Ca2+ overload, which activates the autophagy pathway. Autophagy is an evolutionarily conserved method of cellular self-degradation. Dysregulated autophagy causes inflammation, disruption of the intestinal barrier, and imbalance of intestinal homeostasis, therefore increasing the risk of colonic diseases. This review summarizes the pathogenesis of ERS, UPR, and ERS-related autophagy in UC, providing potential new targets and more effective treatment options for UC.